Affect of Engineered Matrix Environment on Adipogenesis of Adult Adipose-Derived Stem Cells. - Danek, Nicole. (2017)
Abstract: Obesity has become a major concern for today's society over the last decades without any foreseeable solution to the problem. However, it is known that adipose tissue is not just fat storage, and is found to secrete several proteins that regulate every day processes in the body. Studying the process of adipogenesis will help with understanding diseases that stem from obesity. Here, we use a 3D alginate hydrogel system to help understand how cell differentiation is specifically affected by the matrix environment, for a broader application for development of an in vitro model of adipose tissue. Using varying amounts of RGD adhesion peptide within the gels, we aim to change cell morphology of ASCs, and understand it this will have an effect on adipogenesis. Results indicate that the amount of RGD within the gel does affect morphology. Gene expression is higher in gels with RGD than without. Also using this gel system, we aim to show that substrate elastic modulus has an effect on adipogenesis of 3T3-L1 preadipocytes, that is, the higher the elastic modulus, the less adipogenesis will occur. Results show that adipogenesis does appear to be inhibited when cells are in gels with an elastic modulus outside the range of normal adipose tissue; however, more investigation is needed. Overall, results indicate that cell differentiation is influenced by the matrix environment, and shows potential for future studies for adipogenesis, leading to an in vitro model of adipose tissue.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Catherine Kuo.; Committee: Qiaobing Xu, and Kyongbum Lee.; Keyword: Biomedical engineering.